Effect of emission increasing at the generation of low-energy submillisecond electron beam in the diode with the plasma cathodel; High Power Particle Beams (BEAMS) - Koval N. N. Nikolay Nikolaevich; Grigoryev S. V.; Devyatkov V. N.; Teresov A. D.; Schanin P. M. (2008, 2008)
Title screen